Kehamilan Mola Hidatidosa Disertai Hipertiroid - Ria Andriana; Nurul Islamy (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2020)
Thyrotoxicosis is defined as a clinical manifestation of excess thyroid hormone in the circulation. Epidemiological investigations report 0.2% of thyrotoxicosis caused by hydatidiform mole. Mola pregnancy is one of the diseases of the Gestational Trophoblast Disease (GTD), with amenorrhoea and irregular bleeding in the presence of vaginal vesicles. However, this condition can rarely be associated with hyperthyroidism, which may be related to the clinical features of hyperthyroidism. The basic pathogenesis of thyrotoxicosis is the similarity of HCG subunits with TSH which results in excessive stimulation of thyroid hormone. The following is a report of a 23-year-old woman who experienced amenorrhea followed by irregular vaginal bleeding, thyromegaly and abnormal thyroid hormone levels. Transabdominal ultrasound shows signs of molar pregnancy. Evacuation with curettage is done after the serum ?-hCG levels are reduced and thyroid hormone levels are also reduced. Cases and relevant literature are presented here. Keywords: Hydatidiform mole, hyperthyroidism, pregnancy, thyrotoxicosis.